تحولات التلقي في عصر الإعلام الجديد: مقاربة تحليلية في ضوء نظرية التلقي. (Comprehensive Journal of Science, 2025)
This research aims to study the relationship between new media and its role in reshaping the sender –receiver relationship, transforming the recipient from a mere consumer to a partner in the production of meaning. The study is based on the premise that new has not abolished the concept  of reception but rather expanded it, making it an open interpretive process that extends across interconnected digital spaces this research adopted a descriptive approach, drawing on the theoretical frameworks of classical reception theory as formulated by Hans Robert Jauss and Stuart Hall, and attempting to apply them to the contemporary digital environment.
Keywords: New media, reception theory